A cluster analysis of the business models of Spanish journals. Issue 4 (2nd September 2016) - Claudio‐González, Melba G.; Martín‐Baranera, Montserrat; Villarroya, Anna
Abstract : This article provides an analysis of Spanish journals' business models. It presents an integrated approach to the concept of a business model, looking at (1) economics and finances, (2) operation, and (3) the strategic dimensions of the publishing activities. It is based on a cluster analysis of 327 journals that responded to a survey carried out between November 2012 and March 2013. Our findings revealed four business models that differed mostly in the economic and financial dimensions. The greatest difference between the clusters was in the distribution of expenses, and two different operational patterns were revealed by the allocation of staff and volunteer resources. The main barrier to open access was perceived to be financial limitations by three clusters and organizational structure by one cluster, with the subscription‐based journals least likely to be open access or to be tempted to become open access.